A novel fuzzy based controller to reduce circulating currents in parallel interleaved converter connected to the grid - Sravanthy Gaddameedhi; P. Srinivas (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper exhibits suppression strategy of low frequency circulating current components for parallel inter-leaved converters. Here inverters are parallelized by magnetically coupled inductors. Traditionally, carrier interleaved technique was used to get lower distorted output voltage, but it gives a higher circulating currents to flow through the Two-VSC‘s. The mutual inductance of the coupled inductors (CI) is utilized for minimizing circulating currents of high frequency components. Nevertheless, CI can‘t have capability to riddle the components generated by low frequency. When these circulating currents extremely increases may leads to CI saturation, elevated switching losses and diminishes the entire performance of system. Here author identified a novel control technique for a grid-connected parallel inter-leaved converter depending on approach of energy shaping control (ECS). This controller diminishes the value of the low frequency components of circulating current (LFCC). The performance of the proposed circuit is evaluated in simulation mode and correlated with the conventional proportional integral control (PIC) and the linear quadratic control (LQC). The Fuzzy controller is also included in this work to enhance the converter performance effectively and to diminish the circulating currents along with the healthy harmonic performance analysis.